ANALISIS PERMINTAAN PENAMBAHAN UNIT DI RENTAL MOBIL PLESIR JOGJA TRANSPORT DENGAN METODE SIMPLE ADDITIVE WEIGHTING DAN BEST WORST METHOD - Hafiz Firmansyah (JURNAL ILMIAH PENELITIAN MAHASISWA, 2024)
This research aims to analyze the demand for additional units at Plesir Jogja Transport Car Rental using the Simple Additive Weighting and Best Worst methods. Car rental as a transportation service provider is a business that continues to grow, especially in tourist cities like Yogyakarta. In managing a car rental business, management needs to consider requests for additional units to meet customer needs efficiently. With many requests for Inova reborn cars in the last 3 months, namely 63x in 3 months, Toyota Hiace 29x in 3 months, Toyota Avanza 53x in 3 months, Brio 56x in 3 months, Yaris 45x in 3 months. Calculation of the final preference value, which will change the priority of the car unit selection decision, can influence the importance of good criteria weighting. If normalization is not carried out, the Simple Additive Weighting method will produce incorrect preference values because there will be no standardization of values to facilitate subsequent calculations. For each option being tested, it is important to take into account which attributes have benefits or costs to choose the best and worst alternatives. Criteria weighting is very important because interest preferences have a big influence on the final preference value. So creating assessment factors in the criteria will make the decision making process easier. Fuel consumption which has the greatest weight of all the criteria can be seen from the weighting of the criteria produced using the best and worst methods. With a weight value of 0.372709, it is considered the most suitable for adding car units with the lowest weight car price of 0.042769857.